The APOE -219G/T and +113G/C polymorphisms affect insulin resistance among Turks - Komurcu-Bayrak, Evrim; Onat, Altan; Yuzbasiogullari, Berna; Mononen, Nina; Laaksonen, Reijo; Kahonen, Mika; Hergenc, Gulay; Lehtimaki, Terho; Erginel-Unaltuna, Nihan (W B SAUNDERS CO-ELSEVIER INC, 2011)
The -219G/T (rs405509) and +113G/C (rs440446) polymorphisms within the regulatory region of the apolipoprotein E (APOE) gene have been related to the transcriptional activity of the gene. We examined the effect of the stated polymorphisms and their construct haplotypes with the APOE epsilon 2/epsilon 3/epsilon 4 polymorphism on lipid levels and insulin resistance in the Turkish Adult Risk Factor Study. Randomly selected 1774 adults (mean age, 55.0 +/- 11.7 years; 51.2% women) participating in the population-based Turkish Adult Risk Factor Study were cross-sectionally analyzed for the -219G/T, +113G/C, and epsilon 2/epsilon 3/epsilon 4 polymorphisms as well as their haplotypes. Insulin resistance was defined as the 70th percentile in the sample (> 2.51) of the homeostatic model assessment (HOMA). The frequencies of the -219T and +113C alleles were 0.477 and 0.423, respectively; and those of haplotype 1 (GG epsilon 3) and haplotype 2 (TC epsilon 3) were 44.1% and 41.9%, respectively. The -219G/T and +113G/C genotypes (both P < .04) and diplotypes of haplotype 2 (TC epsilon 3) (P < .014) were inversely related to serum fasting insulin and the HOMA index, even after controlling for 8 relevant covariates, but not to serum lipids. Within the APOE3 group, haplotype 2 (TC-/TC+) heterozygotes had an odds ratio of 0.66 (95% confidence interval, 0.42-0.99) for HOMA of insulin resistance after adjusting for 8 covariates. APOE promoter polymorphisms and their diplotypes are independently related with serum fasting insulin levels and HOMA index among Turks. 2011 Elsevier Inc. All rights reserved.
Keywords: APOLIPOPROTEIN-E GENE; PROMOTER POLYMORPHISMS; CARDIOVASCULAR-DISEASE; LDL-CHOLESTEROL; CORONARY; ASSOCIATION; RISK; ATHEROSCLEROSIS; GENOTYPE; OBESITY; Endocrinology & Metabolism